2014
DOI: 10.1038/mp.2014.44
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of compulsivity: a common bias towards learning habits

Abstract: Why do we repeat choices that we know are bad for us? Decision making is characterized by the parallel engagement of two distinct systems, goal-directed and habitual, thought to arise from two computational learning mechanisms, model-based and model-free. The habitual system is a candidate source of pathological fixedness. Using a decision task that measures the contribution to learning of either mechanism, we show a bias towards model-free (habit) acquisition in disorders involving both natural (binge eating)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
598
16
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 595 publications
(682 citation statements)
references
References 47 publications
50
598
16
3
Order By: Relevance
“…There is accumulating evidence that in substance dependence and disorders of compulsivity PIT effects are increased (Garbusow et al, , 2015Hogarth, Field, & Rose, 2013;Glasner, Overmier, & Balleine, 2005) whereas MB control appears to be disrupted Voon et al, 2014). Moreover, MB neural signatures are reduced in high-impulsive individuals (Deserno, Wilbertz, et al, 2015), and impulsivity further seems to be associated with PIT effects (Garofalo & di Pellegrino, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is accumulating evidence that in substance dependence and disorders of compulsivity PIT effects are increased (Garbusow et al, , 2015Hogarth, Field, & Rose, 2013;Glasner, Overmier, & Balleine, 2005) whereas MB control appears to be disrupted Voon et al, 2014). Moreover, MB neural signatures are reduced in high-impulsive individuals (Deserno, Wilbertz, et al, 2015), and impulsivity further seems to be associated with PIT effects (Garofalo & di Pellegrino, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Doll et al, 2016). Most studies have found correlations with the MB but not with the MF component, including cognitive Otto et al, 2013) and emotional (Otto et al, 2013) variables as well as pharmacological challenges Wunderlich, Smittenaar, & Dolan, 2012), brain stimulation (Smittenaar, FitzGerald, Romei, Wright, & Dolan, 2013; but see Smittenaar, Prichard, FitzGerald, Diedrichsen, & Dolan, 2014), and interindividual differences such as age (Eppinger, Walter, Heekeren, & Li, 2013) or psychiatric disorders Voon et al, 2014). Other tasks such as the probabilistic selection task may be more appropriate to specifically assess the MF system (Doll et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Using this framework, it was found that repeated exposure to addictive drugs shifts behavior from model-based to model-free emphasis (Kurth-Nelson and Redish 2011, Lucantonio et al 2012. Likewise, data fitting by the dual-system model revealed that subjects diagnosed with obsessivecompulsive disorder display a bias towards model-free habit acquisition (Voon et al 2014). The central control mechanisms governing the balance maintenance and shifts between model-based and model-free systems represent an area of intense ongoing research (Simon and Daw 2011).…”
Section: Endophenotypes Across Brain Disorder Categoriesmentioning
confidence: 99%
“…Indeed, addictive behaviours and social cognition can be tied together through existing theoretical accounts of addictive behaviours -for example, those based on reinforcement learning 6 and the 'Bayesian brain' hypothesis 7 . Computational modelling has begun to inform empirical studies on decision making in addiction 8,9 , putatively addiction-like disorders 9,10 and risk factors for addiction [11][12][13] . Likewise, computational accounts of social cognition have been tested in neuroscience.…”
Section: I N K To O R I G I N a L A Rt I C L Ementioning
confidence: 99%